An improved hybrid firefly algorithm for capacitated vehicle routing problem - Altabeeb, Asma M.; Mohsen, Abdulqader M.; Ghallab, Abdullatif (Applied soft computing, 2019)
Firefly algorithm (FA) is a new meta-heuristic which is successfully applied to solve several optimization problems. However, it suffers from a drawback of easily getting stuck at local optima. This paper proposes a new hybrid FA, called CVRP-FA, to solve capacitated vehicle routing problem. In CVRP-FA, FA is integrated with two types of local search and genetic operators to enhance the solution’s quality and accelerate the convergence. The experiments are conducted over 82 benchmark instances. The results demonstrate that CVRP-FA has fast convergence rate and high computational accuracy. It significantly outperforms the other state-of-the-art FA variants in majority of the tested instances. •Hybridized firefly algorithm was introduced for capacitated vehicle routing problem.•The hybridization enhances the solution quality and speeds up the convergence of FA.•Better balance between intensification and diversification was achieved.•HFA is a stable and efficient to solve capacitated vehicle routing problem (CVRP).•We show that FA is able to find new best solutions for some of CVRP instances.